2015
DOI: 10.1371/journal.pone.0131585
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a Mannose-6-Phosphate Isomerase from Bacillus amyloliquefaciens and Its Application in Fructose-6-Phosphate Production

Abstract: The BaM6PI gene encoding a mannose-6-phosphate isomerase (M6PI, EC 5.3.1.8) was cloned from Bacillus amyloliquefaciens DSM7 and overexpressed in Escherichia coli. The enzyme activity of BaM6PI was optimal at pH and temperature of 7.5 and 70°C, respectively, with a kcat/Km of 13,900 s-1 mM-1 for mannose-6-phosphate (M6P). The purified BaM6PI demonstrated the highest catalytic efficiency of all characterized M6PIs. Although M6PIs have been characterized from several other sources, BaM6PI is distinguished from ot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 49 publications
0
8
0
2
Order By: Relevance
“…Following transport of mannose into the cell, one pathway for mannose utilization is by isomerization to fructose; however, such isomerases are predominantly found in bacteria and do not exist in yeast ( Rajesh et al, 2012 ; Sigdel et al, 2015 ). Not surprisingly, BLAST analysis revealed no homologs of bacterial mannose isomerases in Y. lipolytica (all BLAST analysis performed under default parameters unless source is noted).…”
Section: Hexose Substratesmentioning
confidence: 99%
“…Following transport of mannose into the cell, one pathway for mannose utilization is by isomerization to fructose; however, such isomerases are predominantly found in bacteria and do not exist in yeast ( Rajesh et al, 2012 ; Sigdel et al, 2015 ). Not surprisingly, BLAST analysis revealed no homologs of bacterial mannose isomerases in Y. lipolytica (all BLAST analysis performed under default parameters unless source is noted).…”
Section: Hexose Substratesmentioning
confidence: 99%
“…Considering that, in addition to gene/protein expression, enzyme activity can also affect their function and cellular response to drug treatment [34]. Cysteine carbazole sulfuric acid method was usually used to test enzyme activity of PMI [26]. First, we found that enzyme activity of PMI in 8305C and 8505C cells decreased when PMI was knocked down (Additional file 2: Fig.…”
Section: Intracellular Zn 2+ Concentration Affects Pmi Activity and The Response Of Thyroid Cancer Cells To Mannosementioning
confidence: 99%
“…Cysteine carbazole sulfuric acid method was used to measure enzyme activity of PMI as described previously [26]. In brief, cells were washed, and then lysed by three freeze-thaw cycles and Ultrasonic cracker on ice.…”
Section: Measurement Of Pmi Enzyme Activitymentioning
confidence: 99%
“…A cancrose tipo A corresponde a forma mais severa da doença, sendo tipicamente da Ásia e causada por Xanthomonas citri subsp. citri (XAC), possuindo a maior gama de hospedeiros cítricos, como por exemplo, a laranja doce (Citrus sinensis), limão (C. limon) e lima ácida (C. aurantifolia) (STALL;SEYMOUR, 1983). É a estirpe que está mais difundida no mundo, atingindo o Japão, Argentina, Brasil, Paraguai, China, entre outros países.…”
Section: O Cancro Cítricounclassified
“…Proudfoot e colaboradores (PROUDFOOT et al, 1994) definiram três tipos de PMIs com base no alinhamento da sequência e propriedades físico-químicas e cinéticas. As enzimas dos mamíferos e da maioria das bactérias pertencem às PMIs do Tipo I, que são proteínas monofuncionais homólogas que catalisam uma única reação de isomerização (PROUDFOOT et al, 1994;PROUDFOOT;PAYTON; (SIGDEL et al, 2015).…”
Section: Fosfomanose Isomeraseunclassified